Public budgeting : program planning and implementation - Lyden, Fremont J.; Miller, Ernest G. (Englewood Cliffs, N.J. : Prentice-Hall, 1982)
Examines changes and tactics of government with respect to patterns, effects, and implications of expenditures.
Includes bibliographical references.
sju 22/01/2019
Loans
Keywords: Program budgeting